UPAYA ASEAN REGIONAL FORUM DALAM MENGHADAPI SENGKETA LAUT CINA SELATAN TAHUN 2021-2023 - Amardi, Muhammad Dhafa; Fuadi, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The South China Sea is a strategic area with a high potential for conflict due to overlapping sovereignty claims, particularly China’s unilateral nine-dash line claim, which conflicts with the interests of ASEAN member states. This region holds strategic value not only economically but also geopolitically, as it involves major powers such as the United States. In this context, ASEAN is understood as a Regional Security Complex that seeks to maintain regional stability through a consensus-based mechanism known as the ASEAN Way, emphasizing cooperation, dialogue, and preventive diplomacy. This study employs a qualitative method with a literature review approach and is grounded in the Regional Security Complex Theory (RSCT), which highlights the interconnectedness among states in addressing regional security issues. Through this framework, the ASEAN Regional Forum (ARF) is analyzed based on four key elements territorial boundaries, anarchic structure, security interaction patterns, and power polarization to understand the security dynamics in Southeast Asia, particularly in the South China Sea. ARF serves to build trust, facilitate preventive diplomacy, and promote regional consensus, although its implementation remains constrained by the principle of non-interference and differing national interests. The findings show that ARF functions as an inclusive dialogue platform through initiatives such as confidence-building measures, maritime meetings, and discussions on the Code of Conduct (CoC). However, concrete results in dispute resolution remain limited due to differing positions among ASEAN members and the influence of strategic rivalry between China and the United States. Thus, ARF’s primary role lies in maintaining diplomatic communication and preventing open conflict escalation, even though it has yet to produce substantive solutions. Keywords: South Cina Sea, ASEAN Regional Forum, Regional Security Complex Theory, Regional Security